The Effect of Financial Report Quality and Human Resource Competence on the Implementation of SAKIP (Government Agencies Performance Accountability System) - Indra Lestary Sukimon; Salju Salju; Suhardi M. Anwar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of the quality of financial reports and the competence of human resources on the implementation of SAKIP (Government Agencies Performance Accountability System). Because in addition to the Financial Reports, each Regional Apparatus is also required to compile a Performance Report. Performance Accountability of Government Agencies is an accountability report of a Regional Apparatus that reflects the success or failure of the vision, mission, in achieving the goals and targets or targets that have been set through the media of periodic accountability. In this regard, it is necessary to develop and implement an appropriate, clear, measurable and legitimate accountability system, which is contained in the Financial Statements. The research method is to use a quantitative research approach through interviews and distributing questionnaires to employees. The population and sample are Echelon III and IV officials in sub-districts throughout Palopo City, along with 100 financial management staff and financial operators. The data analysis method used in this research is multiple linear regression. The results show that the quality of financial reports and the competence of human resources are good, so the application of SAKIP must also be good. Vice versa, if the quality of financial reports and human resource competencies decreases, the application of SAKIP will also decrease.